Analisis Dosis Keluaran Berkas Sinar-X Pesawat Linac Varian Clinac CX Berdasarkan Protokol Dosimetri IAEA TRS 398 - Komang Sugiarta; Ni Nyoman Ratini; Hery Suyanto; Syarifuddin Syarifuddin (Universitas Hamzanwadi, 2022)
Research has been conducted on the Analysis of the X-ray beam output of the Linac varian Clinac CX based on the TRS 398 IAEA. This analysis aims to determine the condition of Linac in Bali Mandara Hospital with reference to the value of 1 cGy equal to 1 MU obtained from the analysis of the ionization chamber, temperature, pressure, polarity effect and ion recombination. The research was conducted with variations of X-ray energy 6 MV and 10 MV. The size of the irradiation field used is (10 x 10) cm with a Source to Surface Distance (SSD) of 100 cm. Based on the results of absolute measurements of the output dose of the Linac Varian Clinac CX X-ray beam at the Radiation Oncology Sub-Installation of the Bali Mandara Hospital with two variations of energy used, the output dose value at 6 MV energy is 1,00138 ???/?? and at 10 MV energy 0,99456 ???/?? with a large deviation of 0,138 % and 0,544 %, respectively, with the obtained deviation meeting the TRS 398 IAEA tolerance limit of ± 3%.